RANCANG BANGUN APLIKASI PEMBELAJARAN BAHASA KANTONIS BERBASIS ANDROID BAGI TKI HONGKONG - PRADIPTA, PRADIPTA; Eniyati, Sri (Information Technology and Telematics, 2018)
ABSTRACT. Cantonese Learning Application For Hongkong Workers Based on Android is a learning information provider facility that can help and facilitate learning Cantonese for female workers who want to work in Hong Kong. This application is made using HTML programming language, PHP, MySQL database, bootstrap framework and AppsGeyser application which is used to convert into the form of an android application.